Зарядженi полiсульфоновi ультрафiльтрацiйнi мембрани, сформованi в присутностi iоногенних поверхнево-активних олiгомерiв - Босак, В.З.; Вакулюк, П.В.; Бурбан, А.Ф.; Ісаєв, С.Д.; Вортман, М.Я.; Клименко, Н.С.; Шевченко, В.В. (Видавничий дім "Академперіодика" НАН України, 2007)
The ultrafiltration polysulfone membranes with charged (positive and negative) surface are formed by the phase inversion method from polysulfone solutions containing ionogenic oligomeric surfactants (IOS). It is determined that the IOS content substantially affects the transport and selective characteristics of the formed membranes.